Artificial Intelligence and 5G Mobile Technology Can Drive Investment Opportunities in Emerging Markets - Mockel, Peter; Makala, Baloko (International Finance Corporation, Washington, DC, 2020)
The intersection of artificial intelligence and 5G mobile technology has enormous potential to deliver dramatic improvements in productivity, efficiency, and cost across business sectors and broader society, delivering innovative products and services not previously possible. Though mainstream applications that combine AI and 5G have yet to emerge, key emerging markets sectors such as agribusiness, healthcare and education will be transformed by the combination of AI and 5G.While many mobile operators remain focused on recouping their investments in previous networkstandards, there is a growing interest in 5G networks globally.